한국 정신건강 서비스의 배경과 정신건강복지법 개정에 따른 정신건강작업치료사의 함의 - 신치환; 유은영; Shin Chihwan; Yoo Eun-Young (대한작업치료학회지, 2022)
서론 : 한국은 1970년대에 들어오면서 급속한 산업화와 도시화가 이루어졌고, 광범위한 사회적 변화가 전 분야에 걸쳐서 발생했다. 이러한 변화로 정신질환자에 대한 다양한 부작용이 발생하면서 정신질환자에 대한 혐오와 낙인, 사회적 편견이 심화되었다. 이에 1995년 12월 30일 정신보건법이 제정되었고, 지속 적인 법률 개정을 통해 전 국민을 대상으로 한 정신건강 증진의 장을 신설하고, 정신질환자의 범위 축소 및 관련 복지서비스 등이 개선ㆍ보완되었다. 본론 : 현재 정신건강 서비스에 대한 국민의 관심과 사회적 수요가 급격히 증가하고 있고, 그에 따른 문제 가 더욱 대두되고 있다. 이에 한국은 정신건강 서비스에 대한 접근성 강화, 정신장애의 조기 발견과 조 기 치료를 위한 정책적 노력이 계속되고 있지만 여전히 해결되어야 할 문제점과 과제들이 산적해 있다. 정신건강 서비스에서 나타나는 다양한 문제점을 해소하기 위해 정신건강전문요원의 역할 확립과 재정립 의 필요성이 언급되고 있지만 한국의 정신건강 지원인력은 해외에 비해 많이 부족한 실정이며, 고용불안 정이나 지속적인 이탈과 각 직역의 전문성이 보장되지 못하는 등 운영의 제한점이 따른다. 현재 한국은 지역사회 정신건강 서비스의 인프라 구축 강화를 마련하기 위해 노력하고 있다. 이를 위해 해외에서는 정신건강작업치료사의 역할을 강조한다. 결론 : 정신건강작업치료사는 필수 인력으로서, 작업치료 고유의 가치를 한국의 정신건강 서비스에 실제로 사용하기에 충분할 만큼 명확한 지식과 기술을 갖추고 있다. 하지만 2022년 정신건강복지법이 개정된 현 시점에서 한국의 정신건강 서비스를 위해 개선되어져야 할 부분들이 많다. 또한 정신건강작업치료사 의 역할과 인력 양성, 교육 등에 대한 내용이 비교적 부족한 실정이다. 따라서 다양한 국가에서 선행되 고 있는 ‘작업치료’ 고유의 전문성을 갖춘 정신건강작업치료사의 인력 배치와 활발한 활용은 한국의 정 신건강 서비스를 보다 효과적이고 성공적으로 이룰 수 있도록 하는 근간이 될 것이다. Introduction: South Korea experienced a rapid period of industrialization and urbanization during the 1970s, and widespread social changes occurred in all fields. As a result of such changes, various side effects, such as mental disorders, feelings of disgust, stigmas, and social prejudices against mental disorders, intensified. Accordingly, on December 30, 1995, the Mental Health Act was enacted, and through various amendments, a forum for the promotion of mental health for all citizens was established. In addition, the scope of mental disorders was reduced, and related welfare services were improved and supplemented. Subject: Public interest in mental health and social demand are rapidly increasing, and associated problems are also on the rise. Accordingly, South Korea continues to create policies to strengthen access to mental health services as well as to detect and treat mental disorders at an early stage. However, numerous problems and tasks remain to be resolved. Although the necessity of establishing and re-establishing the role of mental health specialists has been mentioned to solve various problems regarding mental health services, the number of mental health support personnel in South Korea remains insufficient compared to other nations. In addition, employment instability, continuous departures, and operational limitations prevent a guaranteed level of professionalism. South Korea is currently attempting to strengthen its infrastructure for community level mental health services. To this end, the role of occupational therapists working in mental health has been emphasized abroad. Conclusion: After the revisions of the Act on the Improvement of Mental Health and the Support for Welfare Services for Mental Patients in 2022, there have been many areas that need to be improved in the area of mental health services in South Korea. For this purpose, occupational therapists working in mental health are essential and have the knowledge and skills clear enough to actually apply the values inherent in the occupational therapy provided by mental health services in the country. However, the contents of the role, manpower training, and education of occupational therapists working in mental health are relatively inadequate. Therefore, the allocation and active use of occupational therapists working in mental health with a unique expertise regarding “occupational therapy,” which is provided in various countries, will be the basis for a more effective and successful implementation of mental health services in South Korea.